Safety and efficacy of sofosbuvir and ribavirin for genotype 2 hepatitis C Japanese patients with renal dysfunction. Issue 7 (15th February 2018) - Sho, Takuya; Suda, Goki; Nagasaka, Atsushi; Yamamoto, Yoshiya; Furuya, Ken; Kumagai, Kenichi; Uebayashi, Minoru; Terashita, Katsumi; Kobayashi, Tomoe; Tsunematsu, Izumi; Onodera, Manabu; Meguro, Takashi; et al.
Abstract : Aim: The safety and efficacy of sofosbuvir (SOF) and ribavirin (RBV) have not been well clarified in patients with renal dysfunction because clinical trials have not included such patients. We evaluated the safety and efficacy of SOF and RBV for genotype 2 hepatitis C virus (HCV)‐infected patients with renal dysfunction. Methods: The study included genotype 2 HCV‐infected patients who received SOF and RBV between July 2014 and May 2017. The sustained virologic response (SVR) after the treatment and safety during the therapy were evaluated according to renal function. Results: A total of 231 patients were included in this study. The median age was 62 years old, and 45.9% (106/231) were men. Of the 231 patients, 191 (82.8%) and 40 (17.2%) were classified as having chronic kidney disease (CKD) stages G1/2 and G3, respectively. The overall SVR rate was 97% (224/231). The SVR rates in patients with CKD stages G1, 2, G3a, and G3b were 98.1%, 98.6%, 87.9%, and 100%, respectively, and this therapy was tolerated. Multivariate analysis indicated that renal dysfunction was significantly associated with a non‐SVR (odds ratio, 6.963; 95% confidence interval, 1.494–32.41; P = 0.013). The patients with renal dysfunction were older, had advanced liver fibrosis, lower baseline platelet and hemoglobin levels, and a higher rate of RBV dose reduction. Conclusions: Sofosbuvir and RBV therapy is highly effective and safe for genotype 2 HCV‐infected Japanese patients. However, attention should be paid to baseline renal function when SOF‐ and RBV‐containing regimens are used for patients with renal dysfunction.